EFFECT OF INVESTMENT DECISION AND DIVIDEND POLICY TO THE VALUE OF PT ASTRA ARGO LESTARI TBK IN 2009-2015 - Rukmini, Rukmini; Rusnaeni, N (Universitas Pakuan, 2018)
The purpose of this research was to know the influence of investment decision (TAG) to company value (PBV) of PT Astra Argo Lestari Tbk, to know the influence of dividend policy to PTVVA value, to know influence of investment decision and dividend policy to PT Astra Argo Lestari Tbks value from 2009-2015. Script collection method in this final project was using documentation method, research library, and internet research. While the data analysis method used was descriptive statistical analysis, simple linear regression analysis and multiple hypotheses test. The author conducted a study at the Indonesian Capital Market Electronic Library (ICaMEL) located at the Jakarta Stock Exchange building. The object of study in this research is how big influence of decision of investment and policy of dividend to PT Astra Argo Lestari company value. Based on the result of research using SPSS 23, it is found that investment decision influence 17% to company value, dividend policy influence 45% to company value and investment decision and dividend policy together influence 90,8%. Meanwhile 9.2% other variables were not examined in this study.Â Keywords: Investment Decision, Dividend Policy, Corporate Value